2022
DOI: 10.1155/2022/6458371
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Transit Use during COVID-19 Based on XGB and SHAP Using Smart Card Data

Abstract: As the coronavirus (COVID-19) pandemic continues, many protective measures have been taken in Seoul, Korea, and around the world. This situation has drastically changed lifestyle and travel behavior. An important issue concerns understanding the reasons for giving up transit use and the potential impact on travel patterns during the COVID-19 pandemic. To shed light on these issues that are essential for transit policy, this study explores transit use choice, such as whether users have given-up transit use or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…To summarize, although there has been increasing investigation of metro use adaptation to COVID-19 and mobility intervention policies, several research gaps that deserve further investigation remain. First, compared to studies that examine aggregate metro use response to COVID-19 at levels of metro stations, neighborhoods, and cities ( Carrión et al, 2021 ; Chang et al, 2021 ; Kwon et al, 2022 ; Mützel & Scheiner, 2022 ), few studies have observed the individual-level metro use responses, particularly using a large sample size ( Lee, 2022 ; Park & Cho, 2021 ). The regional or aggregate responses, which are often measured by the ridership change, are not equivalent to individuals' metro use behavioral reactions ( Sy et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…To summarize, although there has been increasing investigation of metro use adaptation to COVID-19 and mobility intervention policies, several research gaps that deserve further investigation remain. First, compared to studies that examine aggregate metro use response to COVID-19 at levels of metro stations, neighborhoods, and cities ( Carrión et al, 2021 ; Chang et al, 2021 ; Kwon et al, 2022 ; Mützel & Scheiner, 2022 ), few studies have observed the individual-level metro use responses, particularly using a large sample size ( Lee, 2022 ; Park & Cho, 2021 ). The regional or aggregate responses, which are often measured by the ridership change, are not equivalent to individuals' metro use behavioral reactions ( Sy et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, the limited attention given to the causality at the individual level might be due to the lack of longitudinal observations of individuals' repeated metro use, particularly right before and after the occurrence of the outbreak and mobility intervention events. Most existing studies rely on data from questionnaire surveys or interviews and transit smart card big data to investigate the associations between the COVID-19 and individual's metro use ( Lee, 2022 ; Maljaee & Sameni, 2022 ; Park et al, 2022 ; Zhou et al, 2021 ). However, these data sources are often difficult to be applied to build rigorous quasi-experimental designs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, models that use the autoregressive integrated moving average (ARIMA) perform well for normal conditions based on the stationary assumption of the time series data, but it is difficult for them to reflect the nonstationary traffic data, especially the nonlinear relationships between traffic variables (2). Non-parametric machine learning methods have been used extensively to overcome the nonlinear problems of statistical models (9,10). However, machine learning models, such as the support vector machine (SVM) and the k-nearest neighbor (KNN), require statistical assumptions to derive manually designed features (8).…”
mentioning
confidence: 99%